ANALYSIS OF DIMETHYLSULFIDE AS BIOGEOCHEMICAL CYCLES SULFUR ON REGIONAL ESTUARY SPERMONDE - Rakhmad Armus; Alfian Noor; Ahyar Ahmad; Muhammad Lukman (Marina Chimica Acta, 2018)
We developed a more accurate method of analysis for low-concentration volatile compounds used for the determination of free dimethylsulfide (DMS) in marine phytoplankton by using solid phase (SPME) gas chromatography - spectrometry Mass of GC-MS and head space method. DMSP, as a product of bacteria degradation has been scientifically recognized to be affected by climate change due to increased in sea surface temperature, and form DMS compunds.. The present study is to determine the DMSP concentration and degradation pathway in the oligotrophic region of Spermonde waters. The spatial and temporal correlation between DMSP degrading bacterial codes and biological potential controls for DMS formation in the open seas was examined using a statistical factorial analysis of variance and regression against the spatial (or distance) gradients of the Spermonde coastal waters, the concentration of chlorophyll-a, and diatom community structures. Seawater chemical properties, chlorophyll-a, and diatom samples were collected from several sites in the Tallo-Makassar river estuary, and the Pangkep river in September 2017 (transitional wet-to-dry-season). The result shows that the concentration of the Domination Index was higher in the transition season of 35.2 to 85.2 μM than in other seasons. The abundance of diatoms during the transition season reached 16,534 plankter / mL.